Exosomal miR-152-5p and miR-3681-5p function as potential biomarkers for ST-segment elevation myocardial infarction - Chen, Xiaozhu; Huang, Fengrong; Liu, Yunhong; Liu, Shujun; Tan, Gangwen (Clinics, 2022)
Background: The strain parameters of Real-Time Three-Dimensional Spot Tracking Echocardiography (RT3D-STE) are GLS, GAS, GRS, and GCS, while each index can significantly diagnose Acute Myocardial Infarction (AMI) patients, but none of them can distinguish between NSTEMI and STEMI. MicroRNAs (miRNAs) play essential roles in Acute Myocardial Infarction (AMI), but little is known about the value of exosome miRNA combined with Real-Time Three-Dimensional Spot Tracking Echocardiography (RT3D-STE) between ST-segment Elevation Myocardial Infarction (STEMI) and Non-ST-segment Elevation Myocardial Infarction (NSTEMI). Aim: To estimate the exosomal miRNAs related to strain parameters of RT3D-STE as biomarkers for early detection of STEMI and NSTEMI. Methods: The present study collected plasma samples from thirty-four (34) patients with AMI (including STEMI and NSTEMI) and employed high-throughput sequence technology and real-time quantitative polymerase chain reaction (RT-qPCR) to identify the differentially expressed miRNAs. The Pearson correlation coefficient is used to measure the strength of a linear association between differentially expressed miRNAs and strain parameters of RT3D-STE. Results: Twenty-eight (28) differentially expressed exosomal miRNAs were universally identified between STEMI, NSTEM, and normal groups. Among them, there are 10 miRNAs (miR-152-5p, miR-3681-5p, miR-193a-5p, miR-193b-5p miR-345-5p, miR-125a-5p, miR-365a-3p, miR-4520-2-3p, hsa-miR-193b-3p and hsa-miR-5579-5p) with a Pearson correlation greater than 0.6 with RT3D-STE strain parameters. Especially, miR-152-5p and miR-3681-5p showed the most significant correlation with RT3D-STE strain parameters. Target genes of these 10 miRNAs are analyzed for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways enrichment, and they were found to be mainly involved in the cellular metabolism processes and HIF-1 signaling pathway. RT-qPCR verified the significant differential expression of miR-152-5p and miR-3681-5p between STEMI and NSTEM groups. Conclusion: RT3D-STE and exosome miRNAs can be used as a hierarchical diagnostic system in AMI. If the RT3D-STE is abnormal, the exosome miRNAs can be detected again to obtain more detailed and accurate diagnostic results between STEMI and NSTEM groups. Exosomal miR-152-5p and miR-3681-5p may serve as potential biomarkers for ST-segment elevation myocardial infarction.